Stroke register in Smolensk Region - G. Yu. Alfimova; N. N. Maslova (Бюллетень сибирской медицины, 2008)
The stroke register having been started in Smolensk Region revealed stroke morbidity 2,38 cases and stroke mortality 1,25 cases for 1000 people in 2007. Stroke-case fatality comprised 33,4%. Hypertension appeared to be the main risk factor of stroke (81%).